2007
DOI: 10.1080/01612840601172577
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Violence Awareness

Abstract: Violence against women is a major influence on women's mental health. We used popular education techniques to train 14 Spanish-speaking women as promotoras (community health workers) to increase awareness about violence against women in low income Texas communities. These women then conducted over 80 presentations in Spanish in local community settings. The impact of the program on the promotoras and on women attending the presentations was evaluated using qualitative methods. This research lends support to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…One of the only published studies examining the work of promotoras in DV revealed preliminary findings of positive consequences for both the promotoras and women who attended their DV presentations (Kelly et al, 2007). Benefits for the promotoras included better communication skills and gaining expert knowledge (Kelly et al, 2007). The present study extends previous research on the promotora model for the field of DV by examining peer leadership development with a group of immigrant Latina women survivors of DV.…”
Section: Extending Promotora Models To Latina DV Survivorssupporting
confidence: 54%
See 3 more Smart Citations
“…One of the only published studies examining the work of promotoras in DV revealed preliminary findings of positive consequences for both the promotoras and women who attended their DV presentations (Kelly et al, 2007). Benefits for the promotoras included better communication skills and gaining expert knowledge (Kelly et al, 2007). The present study extends previous research on the promotora model for the field of DV by examining peer leadership development with a group of immigrant Latina women survivors of DV.…”
Section: Extending Promotora Models To Latina DV Survivorssupporting
confidence: 54%
“…Though limited in its ability to generalize beyond this unique training group, this study extends our current understanding of the impact of promotora -based programs for DV specifically by highlighting how such programs can positively affect DV promotoras themselves (Squires & O’Brien, 2012). Though Latino communities and allies have frequently responded to DV using nontraditional and culturally relevant outreach (Kelly et al, 2007), the present study addresses the lack of studies that document promotora programs that may benefit women living under significant economic and sociopolitical stress, and who also are living with histories of DV. To the knowledge of the authors, this is the first prospective study of a peer leadership program to evaluate the impact of a promotora model training program on immigrant Latina survivors of DV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Promotoras are community members who are trained to provide education and/or guidance for fellow community members (Nemcek & Sabatier, 2003) and serve as liaisons between the community and health care professionals on projects that aim to benefit the community (Elder, Ayala, Slymen, Arredondo, & Campbell, 2009). The use of promotoras and lay health advisors in research studies has been well documented (Kelly, Lesser, Peralez-Dieckmann, & Castilla, 2007) and is considered an effective strategy for reaching underserved communities (Saad-Harfouche et al, 2011). Additionally, promotoras have been successful in addressing uncontrolled HTN and have had positive outcomes in the management and reduction of HTN risks (Sánchez et al, 2014).…”
Section: Background/significancementioning
confidence: 99%